Mikhail Gorbachev : revolutionary for democracy - Sproule, Anna. (Milwaukee : Gareth Stevens Children's Books, 1991)
An account of Mr. Gorbachev's role in the Soviet Union at the present time, as events unfold which portend a much freer way of life for the Russian people.
Includes bibliographical references and index.
9 13 29
Keywords: Gorbachev, Mikhail Sergeevich, -- 1931- -- Juvenile literature; Heads of state -- Soviet Union -- Biography -- Juvenile literature; Soviet Union -- Politics and government -- Juvenile literature; Gorbachev, Mikhail Sergeevich, -- 1931-; Heads of state; Soviet Union -- Politics and government -- 1985-1991.